(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
this article examines the state of the system in the use of the service, freight transport investment resource of the economy in Uzbekistan, how much resource are directed investment, the share of investment in fixed assets and some of the factor that affect the investment premium.